The Search for Correlated Rotation in Sterically Hindered, Multi-n-Bladed CnArnx± (n = 5, 6 and 7) Propellers: From Models to Molecules - Brydges, Stacey (My University, 2003)
Crystallographically independent structures possessing persubstituted cyclopentadiene (C5Ar4X, C5Ar4X2) and -dienyl (C5Ar5) moieties were retrieved from the Cambridge Structural Database, and the torsional angles of selected diaryl frames presented in the form of conformational plots. Semi-empirical (AM1) calculations of the corresponding potential energy surfaces reproduced the conformational trends observed in the solid state. By the Structure Correlation principle, the internal oscillations of nearest (1,2-) and next-nearest (1,3-) aryl rings in all pseudo-propeller subunits were found to be only partially correlated. These solid-state data sets, in combination with energetic predictions of the molecules C5Ph5- 1.18, C5Ph4H- 2.1, C4Ph4C=O 1.53 and C4Ph4CH2 2.2, indicate that a delayed n-ring-flip (where n = 5, X = 0-2 in CnArn-mXm), which is otherwise unobservable via NMR spectroscopic methods, is the threshold rotational mechanism in propeller systems of this type.
The least linear motion path associated with the reorientation of a single terminal phenyl group in the parent C6Ph6, 1.125, has been mapped with the use of semi-empirical molecular orbital, ab initio Hartree Fock and hybrid density functional theory, in combination with numerous basis sets (STO-3G to cc-pVDZ). The superior energetic performance of the less common yet appropriately balanced B3PW91/6-31G(d,p) model chemistry compares favourable with the AM1 Hamiltonian in a conformational analysis of 1.125. To evaluate the energetic and structural implications of replacing a phenyl group with different sterically anisotropic fragments, a series of polyarylated benzenes of the formula C6Ar5X have been synthesized by the Diels-Alder cycloaddition of the appropriate diarylacetylenes to tetraaylcyclopentadienones and subsequent extrusion of carbon monoxide. The X-ray structure determinations of perphenylferrocene (3.19), 1-(pentaphenylphenyl)benzene-2-phenylacetylene (3.26), 1-(1,2-Z-dibromo-2-phenyl)vinyl-2,3,4,5,6-pentaphenylbezene (3.35) and 1-(2-born-2,3-en-2-yl)-2,3,4,5,6-pentaphenylbenzene (3.40) are correlated with the NMR measurements of rotational isomerism in solution.
The solid-state characterization of the heptaphenylcycloheptatrienyl cation, C7Ph7+, 1.139, in [C7Ph7+][CF3CO2]2CF3CO2H, represents the first nondisordered structure solution of a free tropylium cation and ends a formidable, three decade long crystallographic quest. The conformational features of 1.139 and other polysubstituted C7R7-mHm (where 4 ≤ m ≥ 0, R = Ph, Me) derivatives have been rationalized by semi-empirical (AM1) calculations, and reveal a compromise between steric congestion and the fractional loss in aromaticity as the central ring distorts from planarity. A correlation of the 13C-NMR chemical shift with the computed electron density for CnHnx± and CnArnx± species (n = 3 to 7) yields a proportionality factor of approximately 21 and 22 ppm per extra 0.1 electron at the central ring carbons, respectively. The steric capacity of the Diels-Alder cycloaddition reaction has been corroborated by the synthesis of C7Ph6FcH, 4.38, for which the structural perturbations induced by the ferrocenyl fragment were quantified on both static (X-ray crystallography) and dynamic (variable-temperature NMR) levels. Subsequent attempts to study π-delocalization effects in the α-stabilized organometallic cation, [C7Ph6Fc]+, were thwarted by the apparent inaccessibility of the methine hydrogen in 4.38 by appropriate reagents. An X-ray diffraction analysis confirmed the formation of [C7Ph6FcH]+ [SbCl6]-, 4.44, via an electron abstraction at the metal center.
Keywords: Chemistry; Chemistry